PENGARUH KEADILAN ORGANISASIONAL DAN PEMBERDAYAAN PSIKOLOGIS KARYAWAN TERHADAP KOMITMEN ORGANISASIONAL PADA KARYAWAN OPERASIONAL PT. DESTINATION ASIA - Pradnyantara, Kadek Ery; Sintaasih, Desak Ketut (E-Jurnal Manajemen, 2018)
The low organizational commitment reflects the lack of responsibilities of employees in performing their duties. The purpose of this research is to know and analyze the influence of organizational justice and employee empowerment toward organizational commitment at PT. Destination Asia. Population in this research is all employees of PT. Destination Asia in Bali totaling 56 people. The method of determining the sample used in this study is the census technique that is the technique of determining the sample when all members of the population used as a sample, so the sample of this study is selurh operational employees who work PT. Destination Asia. This study uses multiple linear regression analysis techniques to examine the effect of organizational justice and employee empowerment to organizational commitment of employees of PT. Destination Asia. The results showed that organizational fairness and empowerment of employees have a positive and significant impact on organizational commitment of employees of PT. Destination Asia. The results of the questionnaire show that indicators of normative commitment, distributive equity indicators, and impact indicators relate to a person's confidence in their abilities.